Cambridge New Insight into IELTS : Student's Book with Answers - Jakeman, Vanessa and McDowell, Clare (New Delhi Cambridge University Press, 2016)
Comprehensive preparation and practice for IELTS, now updated with fresh, new material
Keywords: International English Language Testing System -- English language -- Vocabulary